2016
DOI: 10.1186/s12955-016-0411-0
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the impact of changes in HbA1c, body weight and insulin injection regimen on health related quality-of-life: a time trade off study

Abstract: BackgroundThere are limited data on the potential short-term benefits associated with reductions in HbA1c levels, and understanding any immediate improvements in health related quality-of-life (HRQoL) through better glycaemic control may help inform diabetes management decisions. This time-trade-off (TTO) study investigated the short-term impact on HRQoL associated with three different aspects of diabetes management; HbA1c change, body weight change, and the complexity of treatment regimen.MethodsThe study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 26 publications
2
31
0
1
Order By: Relevance
“…Several of these utilities have been used previously, whereas others (patient utility relative to HbA 1c reduction and treatment complexity, respectively) were developed specifically for the purpose of this study [58]. The utility score of HbA 1c reduction we used is very close to an equivalent score obtained for type 1 diabetes mellitus [59].…”
Section: Discussionmentioning
confidence: 99%
“…Several of these utilities have been used previously, whereas others (patient utility relative to HbA 1c reduction and treatment complexity, respectively) were developed specifically for the purpose of this study [58]. The utility score of HbA 1c reduction we used is very close to an equivalent score obtained for type 1 diabetes mellitus [59].…”
Section: Discussionmentioning
confidence: 99%
“…DM costs go beyond the direct and indirect costs of the disease to include intangible costs such as pain, anxiety, and worsening of quality of life (QoL). QoL has a great impact on the life of diabetic patients as well as a direct relationship with the maintenance of glycemic control (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that there is a preference for avoidance of injections (both daily and weekly) 38,39 . Oral administration may remove a barrier to treatment intensification, with fear of injection often cited as a reason for therapeutic inertia [40][41][42][43][44] .…”
Section: Discussionmentioning
confidence: 99%